The Iraqi EFL College Instructors' use of Strategies Promoting Active Learning (Journal of the College of Basic Education, 2023)
The rapid developments and the huge accumulation of information and technology have many applications in many fields and at all levels of education. Consequently, at college, there is a need to prepare students with a high level of competence and this surely required engaging them actively in the learning process. The failure of students’ active engagement may be due to college instructors’ “over-reliance” on lecturing as a method of teaching. The aims of the study are to evaluate the use of strategies that promote active learning (AL) by Iraqi EFL college instructors and to identify the difference among instructors according to sex. The population of the study is EFL college instructors at Al- Mustansiryah and Baghdad universities during the academic year2010-2011. The sample consists of 48 instructors. The instrument of the study is a questionnaire which contains 74 items classified into four categories: cognitive, metacoginitve , communication, and socio-affective. After gaining the validity and reliability of the questionnaire, it was delivered to the sample of the study.